The “Bottom-Line” Mentality of Leaders and Subordinates Towards Social Undermining - Noviardi Effendi; M. Rasyid Abdillah; Helwen Heri (SAINS ORGANISASI, 2022)
Securing certain bottom-line results is usually considered beneficial to the profitability of the organization. Organizations have an interest in upholding different goals and values which have different effects on different stakeholders. But adopting a bottom-line mentality encourages simple thinking where employees treat every situation as if only one goal is relevant. In terms of the theoretical model, we use socio-cognitive theory (Bandura, 1977, 1986) to propose that the bottom-line mentality of leaders is positively related to the bottom-line mentality of employees. On the basis of conceptual arguments related to bottom-line mentality (Callahan, 2004; Wolfe, 1988), we hypothesized that leader mentality is positively and significantly related to employee mentality. Likewise with the leader's mentality towards Social Undermining, the two variables are positively related but not significant. On the other hand, subordinate mentality is negatively and insignificantly related to Social Undermining.